QUALITY ASSESSMENT AND SAFETY OF COMMERCIALLY SOLD STEAK MEAT “SUYA” IN IBADAN METROPOLIS: A MENACE TO PUBLIC HEALTH (FUDMA JOURNAL OF SCIENCES, 2024)
The study evaluated the quality and safety of suya—a popular ready-to-eat meat—produce in Ibadan, Nigeria. Suya samples were analyzed from four local government areas: Ibadan North-West (SB), Ibadan North (BD), Oluyole (NG), and Egbeda (EG). The microbial analysis showed significant contamination, with total bacterial counts exceeding recommended limits. Although coliform bacteria were absent, but the presence of Staphylococcus aureusin samples from BD and SB highlighted evidence of poor hygiene. Additionally, Salmonella typhi and Pseudomonas aeruginosa were detected in BD samples, posing foodborne illness risks. Heavy metals were analyzed, with Zinc within safe limit, but chromium significantly exceeded the 1.0 mg/kg limit in all samples. Cadmium was slightly above the threshold in samples from NG and EG. While lead was within acceptable limits. Arsenic was alarmingly high across all the samples. Estimated daily intake (EDI) values for arsenic and chromium indicated significant exposure risks, with arsenic EDI surpassing the provisional tolerable daily intake (PTDI) in all samples. Target hazard quotient (THQ) values for chromium and arsenic were above 1 in most samples, indicating potential health hazards, and Hazard Index (HI) values exceeded the safe threshold in all the samples for non-carcinogenic assessment, indicating a high possibility of adverse health effects. Exposure to arsenic and cadmium has been linked to high cancer risks, according to carcinogenic risk assessment utilizing incremental lifetime cancer risk (ILCR) values; all samples had ILCR values over the acceptable risk range. This study emphasizes the necessity of strict food safety laws, improved hygiene among suya vendors and public...
Keywords: Suya meat; Heavy metals; Microbial quality; Health risk assessment; Carcinogenic; Health Index